(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
We describe and compare three partial skulls of Chinese juvenile Proboscidipparion sinense from the Nihewanian of China. Study of the facial morphology, especially the nasal aperture, as well as cheek tooth morphology and metric data, including length versus width of the maxillary cheek teeth of dP2, 3 and 4, support the conclusion that these skulls are referable to Proboscidipparion sinense. We reaffirm that Proboscidipparion sinense is a member of the “Sivalhippus” Complex that includes the following superspecific clades: Sivalhippus, Eurygnathohippus, Plesiohipparion and Proboscidipparion. Recent studies by Bernor and Sun (2015) suggest that Proboscidipparion is particularly closely related to Chinese Plesiohipparion, and more distantly related to Eurygnathohippus (exclusively Africa) and Sivalhippus (mostly South Asia)